الانتقال المنهجي في النقد الجزائري عبد الملك مرتاض أنموذجا - عزاز, سعاد (جامعة الوادي - university of Eloued, 2020)
إن الحديث عن النقد بالجزائر يحيلنا بالضرورة إلى معرفة أهم المناهج النقدية التي مر بـها هذا الأخير، بهدف تأسيس ورصد راهن الكتابة النقدية في الجزائر؛ فالمنهج يمثل الهاجس الأول لدى الناقد إثر تعامله مع النص الأدبي بحثا عن المعنى والجمالية الأدبية فيه؛ ونقصد بذلك توزع المنهج حسب آلياته وإجرأته بين البحث في الأسباب وما يحيط بهذا النص من عوامل خارجية تمس المؤلف، لتنعكس على نصه، وبين البحث عن تلك العناصر والعلاقات التي تشكل بناء وكيان النص؛ بمعنى البحث في نسقه الداخلي، لنستنتج في الأخير عن طريق الاستدلال والمقارنة بين مجموعة من المؤلفات النقدية "لمرتاض"، كيف أن هذه المناهج قد ساهمت في تحديد الرؤية المنهجية للناقد الجزائري وتعريفه بأهم مواطن الفشل والنجاح، وحتى يتجاوز الآخر ويستحدث نظرية نقدية عربية لم لا؟. الكلمات المفتاحية: السياق؛ النسق؛ النقد الأدبي الجزائري؛ التحول المنهجي. Abstract: Talking about criticism in Algeria necessarily leads us to know the most important critical approaches experienced by the later, in order to establish and monitor the current critical writing in Algeria; the approach represents the first concern of the critic when dealing with the literary text in search of meaning and literary aesthetic in it; we mean by this that The approach is distributed according to its mechanisms and procedures between researching the causes and the external factors surrounding the text that affect the author and which are reflected on his text, And the search for those elements and relationships that constitute the structure and entity of the text; which means to search in its internal harmony, we can deduce that by inference and the comparison of a collection of literary criticism "Abdul Malek Murtad""، How these approaches have contributed to define the methodological vision of the Algerian critic and his definition of the most important failures and successes , In order to go beyond the other and develop an Arab critical theory, why not ? .key words: context;, format; Algerian literary criticism; systematic transformation.
مقال
Keywords: السياق؛ النسق؛ النقد الأدبي الجزائري؛ التحول المنهجي: context, format; Algerian literary criticism; systematic transformation.